“The package has been opened”- parents' perspective and social validity of an Early Start Denver Model intervention for young children with autism - Carlsson, Emilia; Nygren, Gudrun; Gillberg, Christopher; Linnsand, Petra (Frontiers in Child and Adolescent Psychiatry, 2024)
Introduction This study aimed to capture experiences and perspectives of parents of children with autism participating in an intervention program based on the Early Start Denver Model (ESDM). Specifically, we wanted their views regarding feasibility, acceptability, and significance of the intervention program, i.e., its social validity. Methods Fourteen parents, whose children has been diagnosed with autism, were interviewed. Results The results included three themes (1) Comprehensive approach: the participants emphasized the importance of early detection and interventions in their local setting in close cooperation between themselves, health care professionals, and preschool staff. They also highlighted the individual goals based on the child's needs in different developmental areas, as well as the whole family's needs and prioritizations. (2) Hands on—available locally and accessible: focused on different aspects of procedures, including features of the ESDM, parent education, the parent-therapist relationship and nearby location. (3) Sense of empowerment—parents got increased knowledge: the intervention was significant within family daily living and daily activities. The participants expressed that the interventions program contributed to an increased knowledge about autism and the ESDM strategies, positively impacted their child, and improved the collaboration with the preschool. Conclusion Parents emphasized the naturalistic, comprehensive, and local setting of the intervention and described that they had gained new knowledge as well a sense of empowerment. The results indicated that the intervention program based on the ESDM was socially valid according to parent descriptions.